Основные результаты комплексных исследований ЮгНИРО в Азово-Черноморском бассейне и Мировом океане в 1994 году - Yakovlev, V.N.; Southern Scientific Research Institute of Marine Fisheries and Oceanography (YugNIRO) (YugNIRO, 1995)
The main results of YugNIRO complex researches in marine living resources state with regard for anthropogenic influence are presented. Prospects for marine culture rational development, microalga culture and further study of biochemichal composition, medicinal properties and antioxidant activity of hydrobiota preparations and opportunities for creation of an industry brunch in the Crimea for their output. Assessment of state and prospects in Ukrainian fishery development in international legal aspect is given. Представлены результаты комплексных исследований ЮгНИРО состояния морских живых ресурсов с учетом антропогенного влияния. Рассмотрены перспективы рационального развития марикультуры, культивирования микроводорослей и дальнейшего изучения биохимического состава, лечебных свойств и антиоксидантной активности препаратов из гидробионтов, а также возможности создания в Крыму отрасли по их производству. Дана оценка состояния и перспектив развития рыболовства Украины в международно-правовом аспекте. Published